Response of Siliceous Marine Organisms to the Permian-Triassic Climate Crisis Based on New Findings From Central Spitsbergen, Svalbard - Foster, W. J.; Asatryan, G.; Rauzi, S.; Botting, J. P.; Buchwald, S. Z.; Lazarus, D. B.; Isson, T.; Renaudie, J.; Kiessling, W. (Paleoceanography and Paleoclimatology, 2023)
Siliceous marine ecosystems play a critical role in shaping the Earth's climate system by influencing rates of organic carbon burial and marine authigenic clay formation (i.e., reverse weathering). The ecological demise of silicifying organisms associated with the Permian-Triassic mass extinction is postulated to have elevated marine authigenic clay formation rates, resulting in a prolonged greenhouse climate during the Early Triassic. Yet, our understanding of the response of siliceous marine organisms during this critical interval is poor. Whilst radiolarians experienced the strongest diversity loss in their evolutionary history and perhaps also the greatest population decline of silica-secreting organisms during this event, only a small number of Griesbachian (post-extinction) localities that record siliceous organisms are known. Here, we report newly discovered latest Changhsingian to early Griesbachian (Clarkina meishanensis - Hindeodus parvus Zone) radiolarians and siliceous sponge spicules from Svalbard. This fauna documents the survival of a low-diversity radiolarian assemblage alongside stem-group hexactinellid sponges making this the first described account of post-extinction silica-secreting organisms from the Permian/Triassic boundary in a shallow marine shelf environment and a mid-northern paleolatitudinal setting. Our findings indicate that latitudinal diversity gradients for silica-secreting organisms following the mass extinction were significantly altered, and that silica productivity was restricted to high latitude and deep water thermal refugia. This result has potential to further shape our understanding of changes in marine dissolved silica levels and in turn rates of reverse weathering, with implications for our understanding of carbon cycle dynamics during this interval. First occurrence of siliceous sponges and radiolarians (biogenic silica) from a mid-northern paleolatitude following the mass extinctionEvidence that extinction survivors show poleward range shifts in response to thermal ...